2020
DOI: 10.3390/app10082913
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Noise Emitted by Vehicles on Pedestrian Crossing Decision-Making: A Study in a Virtual Environment

Abstract: When crossing a road, pedestrians must detect traffic, combine data coming from different perceptual modalities, evaluate the time envelope for safely cross the street, and monitor the position of oncoming vehicles to perform corrective actions if needed. This study analyzed the influence of noise emitted by vehicles, or its absence, on pedestrians’ crossing decision-making. Experiments were performed in a virtual environment using two road scenarios. Participants were presented with stimuli of approaching veh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…At last, regarding the audio-visual and the merely visual stimuli, participants relied mostly on the visual information they received from the approaching vehicle to estimate the available crossing time, contradicting Barton et al (2012) and agreeing with the conclusions of Pugliese et al (2020) and Soares et al (2020). These results prove that the absence of the audio component regarding the road traffic does not compromise the results obtained in pedestrian safety studies performed in a virtual environment.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…At last, regarding the audio-visual and the merely visual stimuli, participants relied mostly on the visual information they received from the approaching vehicle to estimate the available crossing time, contradicting Barton et al (2012) and agreeing with the conclusions of Pugliese et al (2020) and Soares et al (2020). These results prove that the absence of the audio component regarding the road traffic does not compromise the results obtained in pedestrian safety studies performed in a virtual environment.…”
Section: Discussionmentioning
confidence: 51%
“…They verified that participants were faster to respond under the time-constrained condition, which also favoured a distance-based decision. It is possible that, in this study, the higher speeds and close distances have prompted a similar sense of urgency, which is known to accelerate decision processes, although at the cost of accuracy in judgments (Soares et al, 2020). This agrees with Beggiato, Witzlack, Springer, F. Soares et al and Krems (2018), who analysed the effect of daytime, approaching vehicle speed and pedestrian's age on the time gaps accepted to cross the road, and found that the participants took more risky crossing decisions, accepting lower time gaps with the increasing vehicle speed.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations